2009
DOI: 10.1080/17429140802193178
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus ameliorates crop productivity, photosynthesis, nitrate reductase activity and nutrient accumulation in coffee senna (Senna occidentalisL.) under phosphorus-deficient soil

Abstract: Coffee senna (Senna occidentalis L.) plants were subjected to five phosphorus levels: 0, 25, 50, 75 and 100 mg P per kg soil (P 0 , P 1 , P 2 , P 3 and P 4 , respectively). A pot culture experiment was conducted in a net house, AMU, Aligarh, India, under phosphorus-deficient soil. The present data indicates that soil-applied phosphorus significantly ameliorates most of the attributes studied. Out of five phosphorus levels, 75 mg P per kg soil (P 3 ) proved best and enhanced fresh and dry weights, total chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 23 publications
1
11
0
1
Order By: Relevance
“…Additionally, the increase in leaf-NR activity with increasing ISA concentration in the present investigation is in agreement with the findings reported by Naeem et al (2011) in the case of Mentha arvensis L. Similarly, Aftab et al (2011) reported ISA-mediated increase in overall plant growth and other yield and quality parameters in Artemisia annua L. Regarding the positive effect of P on leaf-NR activity, our results find support from the studies on maize (de Magalhaes et al, 1998) and beans (Gniazdowaska et al, 1999), which confirm enhanced assimilation of leaf-NO 3 − content due to P application. In conformity with our results, enhancement in leaf-NR activity with phosphorus application has been reported by several workers in different medicinal and aromatic plants such as Cassia tora (Naeem and Khan, 2005), Cyamopsis tetragonoloba L. (Burman et al, 2007), Senna occidentalis L. (Naeem and Khan, 2009), Cassia tora L. (Naeem et al, 2009a) and Cassia sophera L. (Naeem et al, 2009b).…”
Section: Nitrate Reductase (Nr) Activitysupporting
confidence: 94%
“…Additionally, the increase in leaf-NR activity with increasing ISA concentration in the present investigation is in agreement with the findings reported by Naeem et al (2011) in the case of Mentha arvensis L. Similarly, Aftab et al (2011) reported ISA-mediated increase in overall plant growth and other yield and quality parameters in Artemisia annua L. Regarding the positive effect of P on leaf-NR activity, our results find support from the studies on maize (de Magalhaes et al, 1998) and beans (Gniazdowaska et al, 1999), which confirm enhanced assimilation of leaf-NO 3 − content due to P application. In conformity with our results, enhancement in leaf-NR activity with phosphorus application has been reported by several workers in different medicinal and aromatic plants such as Cassia tora (Naeem and Khan, 2005), Cyamopsis tetragonoloba L. (Burman et al, 2007), Senna occidentalis L. (Naeem and Khan, 2009), Cassia tora L. (Naeem et al, 2009a) and Cassia sophera L. (Naeem et al, 2009b).…”
Section: Nitrate Reductase (Nr) Activitysupporting
confidence: 94%
“…Several studies have suggested that P application enhances the response to drought by improving growth under conditions of water scarcity (dos Santos et al , Garg et al , Campbell and Sage ). P application has shown significant positive effects on photosynthesis, stomatal conductance, membrane stability and water use efficiency (dos Santos et al , dos Santos et al , Naeem and Khan , Faustino et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of P fertilizer reduces its deficiency in soil, increases the stress-tolerating ability of plants ( Cortina et al, 2013 ) and results in adjustments of physiological, morphological, and biochemical processes that increase plant growth ( dos Santos et al, 2004 ; Jones et al, 2005 ; Campbell and Sage, 2006 ; Faustino et al, 2013 ; Liu et al, 2015 ). Despite the importance of P in plant productivity, relatively few studies have assessed its effects on plant physiological and ecological processes under drought stress ( dos Santos et al, 2006 ; Naeem and Khan, 2009 ; Fleisher et al, 2012 ; Jin et al, 2015 ; Liu et al, 2015 ). Most of these studies examined the relationship between P application and physio-biochemical adjustments under drought stress in non-woody plants (mostly crop species).…”
Section: Introductionmentioning
confidence: 99%